Analisis Kandungan Serat Kasar Pada Tepung Porang - Anggela Anggela; Yamaysyah Salma Nabila; Rahmatia Ananda; Eris Pransiscah Nainggolan; Wahyu Wahyu; Asrul Asrul (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
Porang flour, extracted from the tuber of the porang plant (Amorphophallus muelleri), is known as a food ingredient rich in fiber and low in calories. This study aims to measure the crude fiber content in porang flour tested at the Food and Agricultural Product Technology Laboratory, Faculty of Agricultural Technology, Universitas Gadjah Mada. Based on the analysis, the average crude fiber content in porang flour was found to be 0.79%, with a standard deviation of 0.02%. However, no crude fiber content was found in the porang flour gel sample. These findings provide important insights into the potential of porang flour as a fiber source in the development of food products. The results also demonstrate product quality consistency, which can serve as a foundation for the development of healthier food industries.